Families, Relational Scenarios and Emotions in the Time of the COVID-19 Pandemic - Musolino, Santina (Italian Sociological Review, 2020)
This paper will focus on the impact that the COVID-19 emergency and the policies and decisions taken to deal with it (mostly lockdown and social distancing) have had on interpersonal relationships. In particular, it will explore the changes and relational scenarios which have emerged within the patterns of daily family life in the context of a temporary social deprivation caused by the pandemic. To explore this topic, the following contribution will draw on the most recent scientific literature on the COVID-19 pandemic and its effects moving within the theoretical framework of the sociology of emotions. The paper will also discuss how the exploration of emotional life, given its relational nature, can offer interesting sociological reflections on the consequences of COVID-19 on individuals’ perceptions of others and, in doing so, can also suggest new research paths to follow.